Resolving Intellectual Property Disputes - Alavi, Hamed (LeXonomica, 2017)
Within recent decades, increasing the complexity of international trade has resulted in changing many dimensions of doing business with other nations and relevant problems to it. Rising the importance of intellectual property rights as intangible assets of companies is considered among most important characters of modern business process which applies to multinational enterprises and other forms of companies who intend to enter the global market place equally. Benefiting from global marketplace and at the same time protecting IPRs is a difficult goal to achieve due to intangible and diverse nature of such rights which results. In practice of international trade, there is high probability for companies to face with IPR related disputes. Therefore, choice of proper IP Dispute Resolution mechanism is an important step in designing overall IP strategy of the firm as an improper IP dispute resolution method can impose high financial costs as well as affecting reputation of the firm. Current paper tries to answer to the question of what is the most suitable dispute resolution method for IP related disputes. And in order to achieve this objective, paper explores different types of IP disputes, different approaches for resolving IP disputes, factors affecting the choice of method for resolving IP disputes and finally, it will analyse application of dispute resolution mechanisms in different types of IP related disputes.